Alternativas para o desenvolvimento de uma efetiva cultura socioambiental como compromisso social além do âmbito empresarial - Salles, Ézio José Ribeiro de (My University, 2014)
The aim of this study is to demonstrate the need for development of public policies, with incentive mechanisms on the part of the public authorities, in particular, by the municipalities, so that the business community may, upon any consideration, not only comply with the legislation, but also maintain communities sensitizing projects, with regard to care for the environment. Given the importance of environmental concern, not only in Brazil, but worldwide, there were several alternatives for the creation of some kind of effective not just aware the population, but that essentially promotes actual prevention and preservation of the environment, or at least, stimulate the conscious use of environmental resources. This form of protection should require a smaller negative human intervention in the environmental sphere, for which remediation is inevitable for the satisfaction of human needs and for the so-called sustainable development. For it became possible, today, the implementation and the adoption of instruments and environmental alternatives, in this sense, it is essential that companies are obligated to use means less degrading to the environment. Alternatively to inhibit production of goods polluters, the environmental taxes are being applied effectively in many countries. Their experiences have presented great consequences for the State, society, business and the environment, which should be widely studied and put into practice at the national level. It is important to highlight that these practices are permitted by extra taxation. Knowing the inability of most companies to undertake, in a manner fully ecological and not voluntarily, even if they do for any other reason, the State must do its role as interventionist in the economy, so that access to the "sustainable development" may be provided. It is important that companies and the State have environmental behaviors, because their attitudes involve the entire population, both Brazilian and also the world, i.e. all disasters and damage to the environment are reflected in men and even across the globe, with irreparable consequences. So that this awareness may be possible, one of the forms created to introduce the environmental defense in human conduct was environmental taxation, since that the tribute is a factor that may have dual function to pause the consequences in the environmental sphere of uncontrolled economic development and in the reality of current consumption, providing an alternative to the muchvaunted compatibility between economic development and environmental protection. Environmental taxation proves skillful instrument, easier and less costly control for all involved, since implemented according to the reality of each society and its legislation.
O objetivo deste trabalho é demonstrar a necessidade de desenvolvimento de políticas públicas, com mecanismos de incentivo por parte do poder público, em especial, por parte dos municípios, para que o meio empresarial possa, mediante alguma contrapartida, não só cumprir a legislação, mas também manter projetos de sensibilização de comunidades, no que diz respeito aos cuidados com o meio ambiente. Dada a importância da preocupação ambiental, não apenas em nível de Brasil, mas na escala mundial, várias foram as alternativas para a criação de algum meio efetivo que não apenas conscientizasse a população, mas que, essencialmente, promovesse condutas reais de prevenção e preservação do meio ambiente, ou que, ao menos, estimulasse o uso consciente dos recursos ambientais. Essa forma de proteção deve exigir uma menor intervenção humana negativa na esfera ambiental, cuja reparação dos danos é inevitável para a satisfação das necessidades humanas e para o chamado desenvolvimento sustentável. Para que se tornasse possível, hoje, a implementação e a adoção de instrumentos e alternativas ambientais, nesse sentido, é mister que sejam as empresas obrigadas à utilização de meios menos degradantes ao meio ambiente. Como alternativa para inibir a produção de bens poluidores, os tributos ambientais estão sendo aplicados de forma eficiente em muitos países. Suas experiências têm apresentado ótimas consequências para o Estado, sociedade, empresas e para o meio ambiente, as quais deveriam ser amplamente estudadas e colocadas em prática no âmbito nacional. É importante destacar que estas práticas são permitidas pela extrafiscalidade. Sabendo-se da impossibilidade da maioria das empresas em proceder, de uma forma integralmente ecológica não voluntária e, mesmo que o façam por qualquer outra razão, o Estado deve fazer o seu papel de interventor na economia, para que esse acesso ao “desenvolvimento sustentável” seja oportunizado. É importante que as empresas e o Estado tenham condutas socioambientais, pois suas atitudes envolvem toda a população, tanto brasileira quanto mundial, ou seja, todas as catástrofes e danos ao meio ambiente são refletidas nos homens e, até mesmo, em todo o planeta, com consequências irreparáveis. Para que essa conscientização seja possível, uma das formas criadas para se introduzir a defesa ambiental na conduta humana foi a tributação ambiental, já que é o tributo um fator que pode ter dupla função para pausar as consequências na esfera ambiental do desenvolvimento econômico descontrolado e na realidade de consumo atual, propiciando uma alternativa para a tão sonhada compatibilização entre desenvolvimento econômico e proteção ambiental. A tributação ambiental se revela instrumento hábil, de controle mais fácil e menos oneroso para todos os envolvidos, desde que implementada de acordo com a realidade de cada sociedade e respectiva legislação.
Keywords: Desenvolvimento sustentável; Responsabilidade social da empresa; Meio ambiente; Direito ambiental